2005
DOI: 10.1177/1077801205278046
|View full text |Cite
|
Sign up to set email alerts
|

Child Custody and Visitation Decisions When the Father Has Perpetrated Violence Against the Mother

Abstract: This research evaluated the effectiveness of statutes mandating a presumption against custody to a perpetrator of domestic violence (DV) and judicial education about DV. Across six states, the authors examined 393 custody and/or visitation orders where the father perpetrated DV against the mother and surveyed 60 judges who entered those orders. With the presumption, more orders gave legal and physical custody to the mother and imposed a structured schedule and restrictive conditions on fathers' visits, except … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 17 publications
0
48
0
3
Order By: Relevance
“…On the contrary, the data that exists indicates that some form of joint custody appears to be the most common outcome of contested custody litigation. Among the exceptions to joint custody, several studies have found that it is fathers, not mothers, who more often win sole custody (Massachusetts Supreme Judicial Court, 1990;Morrill, Dai, Dunn, Sung & Smith, 2005). 13 Nonetheless, the view of fathers as the underdogs in custody court persists.…”
Section: Historical Perspective 241mentioning
confidence: 99%
“…On the contrary, the data that exists indicates that some form of joint custody appears to be the most common outcome of contested custody litigation. Among the exceptions to joint custody, several studies have found that it is fathers, not mothers, who more often win sole custody (Massachusetts Supreme Judicial Court, 1990;Morrill, Dai, Dunn, Sung & Smith, 2005). 13 Nonetheless, the view of fathers as the underdogs in custody court persists.…”
Section: Historical Perspective 241mentioning
confidence: 99%
“…En plus du blâme social associé au fait d'avoir exercé de la violence envers une femme et du risque de compromettre la qualité de la relation avec leur conjointe (ou ex-conjointe) et leurs enfants, cette violence entraînerait, pour plusieurs d'entre eux, des conséquences d'ordre judiciaire, impliquant des coûts importants pour ces conjoints comme pour la société. On parle ici, entre autres, d'épisodes d'arrestation, de détention et de probation (MSP, 2011 ;Morril et al, 2005 ;Statistique Canada, 2004 (Laing et al, 2013 ;Lupri et Grandin, 2004). De même, il est important d'étudier davantage les besoins spécifiques des femmes qui exercent de la violence (Damant et al, 2014 ;Dowd et Leisring, 2008 ;Swan et al, 2008).…”
Section: Construction De La Violence Conjugale Comme Un Problème Sociunclassified
“…Par ailleurs, deux études (Kernic et al, 2005;Morrill et al, 2005) basées sur de larges échantillons de dossiers de garde montrent que le système de justice peine à détecter la violence conjugale et à mettre en place des mesures adéquates pour protéger les victimes dans les ordonnances concernant la garde et les droits d'accès. Ces chercheurs expliquent ces résultats par le manque de coordination de l'information et des services d'une cour à l'autre (cour criminelle et celle traitant des affaires familiales).…”
Section: Les Séparations Hautement Conflictuellesunclassified